Dietary vitamin A modifies the gut microbiota and intestinal tissue transcriptome, impacting intestinal permeability and the release of inflammatory factors, thereby influencing Aβ pathology - Wang, Zhong-Li; Pang, Shao-Jie; Zhang, Kai-Wen; Li, Peng-Yu; Li, Peng-Gao; Yang, Chun (Frontiers in Nutrition, 2024)
This study aimed to investigate how dietary vitamin A affects the gut microbiota and intestinal tissue, influencing intestinal permeability, inflammatory factors, and Aβ pathology. The APP/PS1-AD mouse model was used, and mice were fed different vitamin A diets for 12 weeks. The groups included vitamin A-deficient (VAD), normal vitamin A (VAN), and vitamin A-supplemented (VAS). No significant changes in food intake and body weight were observed among the groups. However, the VAD and VAS groups showed reduced food intake compared to the VAN group at various time points. In terms of cognitive function, the VAN group performed better in the Morris Water Maze Test, indicating superior learning and memory abilities. The VAD and VAS groups exhibited impaired performance, with the VAS group performing relatively better than the VAD group. Serum vitamin A concentrations differed significantly among the groups, with the VAS group having the highest concentration.Aβ levels were significantly higher in the VAD group compared to both the VAN and VAS groups. Microbial analysis revealed that the VAS and VAN groups had higher microbial diversity than the VAD group, with specific taxa characterizing each group.The VAN group was characterized by taxa such as Actinohacteriota and Desulfovibrionaceae, while the VAD group was characterized by Parabacteroides and Tannerellaceae. The VAS group showed similarities with both VAN and VAD groups, with taxa like Desulfobacterota and Desulfovibrionaceae being present. The VAD vs. VAS, VAD vs. VAN, and VAS vs. VAN comparisons identified 571, 313, and 243 differentially expressed genes, respectively, which associated with cellular and metabolic processes, and pathway analysis revealed enrichment in pathways related to chemical carcinogenesis, drug metabolism, glutathione metabolism, and immune-related processes. The VAD group exhibited higher levels of D-lactate, diamine oxidase, and inflammatory cytokines (TNF-α, IL-1β, IL-6) compared to the VAN and VAS groups. In conclusion, dietary vitamin A modulates the gut microbiota, intestinal permeability, inflammatory factors, and Aβ protein formation, providing insights into AD and potential therapeutic avenues for further investigation.